The Dynamics and Themodynamics of Compressible Fluid Flow : Volume II - Shapiro, Ascher H. (The Ronald Press Company, 1954)
Part V: Supersonic flow continued). Part VI: Mixed flow. Part VII: Unsteady motion in one dimension. Part VIII: Flow of real gases with viscosity and heat conductivity.